Nausea and Vomiting of Early Pregnancy - Basama, Faisal M. S.; Antoniou, Antonios (Gezira Journal of Health Sciences; Vol 14 No 1 (2018), 2018)
Nausea and vomiting in early pregnancy is very common. The severest form, hyperemesis gravidarum,is important as mismanagement can lead to Wernicke’s encephalopathy, central pontine myelosis and death. There is a lack of high-quality evidence in the management of nausea and vomiting in early pregnancy and in the safety of the commonly used drugs, especially the reported side effects and their management. Pregnancies following bariatric surgery are becoming more frequent and care should be taken managing nausea and vomiting in this group since thiamine is primarily absorbed in the small intestine, and Wernicke’s encephalopathy has been described following some types of bariatric surgery. Severe cases of hyperemesis gravidarum warrant caution as Wernicke’s has been described following total parenteral nutrition,and it must be remembered that thiamine needs to be supplemented in this group. The etiology remains unknown and there is scope for research in this area.